Damage evolution of tunnel lining with steel reinforced rubber joints under normal faulting: An experimental and numerical investigation. (March 2020) - Yan, Gaoming; Shen, Yusheng; Gao, Bo; Zheng, Qing; Fan, Kaixiang; Huang, Haifeng
Highlights: A new type of joint for mountain tunnels crossing active faults is proposed. An experimental and numerical investigation on the behaviors of tunnel with the joints. The numerical model manags to obtain the damage evolution of the tunnels. A numerical and experimental comparison show a good agreement of results. Abstract: The zones where tunnels through the active faults are proved to be seriously damaged because of the fault dislocation which could be due to strong earthquakes. A steel reinforced rubber joint with flexibility and ductility is proposed in this paper. An experimental investigation of the responses and the damage patterns of the tunnel lining with the joints under normal faulting is presented. The results showed the damage of the lining with the joints in the model test was mainly concentrated in the fault areas because of the joints' adjustment. No obvious shear failure was found in this test. Then, a nonlinear three-dimensional finite element (FE) model, using concrete damaged plasticity model, was performed to simulate the tunnel linings with the proposed joints and without joints under normal faulting. The numerical results show that the tunnel with the joints had step-like displacements without big relative displacement compared to the tunnel without joints. The joints efficiently decreased the maximum relative displacement between lining segments. The extent of the tensile damage area of the lining affected by normal fault was longer than that of the compressive damage area. And the tensile damage area was larger than the compressive damage area for either the lining with the joints or the lining without joints. There was no obvious difference in damage to the lining with and without joints in areas under compression loading. The joints efficiently decreased the extent of the damage in the zone with tensile stresses. The comparisons between the numerical predictions and experimental results show a good agreement.